Progress in Education for Students with Intellectual Disabilities in Saudi Arabia: Evaluating Status - Alshamri, Khalid H. (Journal of the American Academy of Special Education Professionals, 2020)
A systematic review of the literature was conducted in order to assess the current state of education in Saudi Arabia for students with intellectual disabilities in comparison with the rest of the developed world. It was found that the country has been able to keep up with technological advancements in the area, particularly with intensive application of assistive learning technologies in the classroom and has adopted an inclusive learning philosophy in its approach to helping students with intellectual disability. However, further progress is needed in pedagogical and social fronts of development, particularly in terms of training teachers and orienting parents effectively to address educational needs of students with intellectual disabilities.